SOCIO-PHILOSOPHICAL ANALYSIS OF RELIGIOUS CONSCIOUSNESS IN MODERN SOCIETY - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article discusses a number of current trends in the religious consciousness under the influence of modernization; the researchers analyzed the views of the past and present for the future of religious consciousness.